Effects of thymoquinone and thymoquinone-loaded nanostructured lipid carrier on hepatocellular carcinoma cell models, Hep3B and HepG2 - Haron, Aminah Suhaila (2017)
Hepatocellular carcinoma (HCC) is the fourth most common solid tumor. Dysregulated cell proliferation and tumorigenesis of HCC is commonly associated with chronic hepatitis B infection. Thymoquinone (TQ), a bioactive compound found in Nigella sativa has been shown to exhibit anti-tumor properties. However, due to some limitations of discomfort, high cost and sterility, it was synthesized into Thymoquinone-loaded nanostructured lipid carrier (TQ-NLC) (PATENT NO: PI2012001818) to improve the bioavailability and cytotoxicity of TQ. As cellular models for in vitro liver cancer and toxicity studies, HepG2 and Hep3B are the two most frequently used liver cancer cells. This study aims to determine the differential effects of TQ and TQ-NLC on the different genomic sequence of liver cancer (Hep3B and HepG2 cell lines) as well as to identify the molecular mechanisms underlying its anticancer activities. TQ or TQ-NLC inhibited the growth of both models of human liver cancer cells. The IC50 obtained for Hep3B treated TQ or TQ-NLC at 24 hours was 16.7±2.86 μM and 13.5±3.58 μM respectively. While in HepG2 treated TQ or TQ-NLC at 24 hours, the IC50 obtained was 47.7±0.64 μM and 24.0±0.70 μM respectively. TQ-NLC was observed to be more toxic towards Hep3B cells with IC50 of 9.20 ± 2.25 μM compared to TQ with IC50 of 11.1 ± 0.41 μM at 72 hours of treatment. Meanwhile, IC50 of Hepg2 treated TQ-NLC was 25.5 ± 8.40 μM compared to TQ which was 41.8 ± 6.20 μM at 72 hours of treatment. Overall treatment showed both TQ and TQ-NLC were more toxic towards liver cancer cells compared to normal 3T3 with IC50 >30uM (P<0.05). The increased effectiveness of TQ-NLC maybe related to the encapsulation of TQ that increased its efficiency and toxicity. There was significantly higher percentage of apoptotic cells in Hep3B cells treated with TQ-NLC compared to HepG2 cells. Molecular analysis demonstrated response of Hep3B may be influenced by the level of GSH and Nrf2/Keap1 expression that governed by the ROS status. In HepG2 cells, ROS levels increased with the increased of GSH and Nrf2 upon treatment with TQ or TQ-NLC. By contrast, TQ-NLC reduced the level of ROS in Hep3B cells. TQ also increased GSH level as early as 12 hours in Hep3B cells. The expression of caspase-3 and caspase-7 suggested that both TQ and TQ-NLC may induce apoptosis via intrinsic pathway in both liver cancer cell models. Thus, this study demonstrated TQ and TQ-NLC has in vitro anti-cancer effects in human liver cancer cells and the differential effects appear to be linked to the differential sensitivity towards ROS production.